Laboratory experimental studies of the multiphase separator - M.M. Liakh, E.V. Youriev, B.V. Kopey, T.A. Kryvonozhko (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2018)
In this paper we have characterized the vortex type separator for the four-phase mixture separation in traditional system of separation and redesign or improvement of the vortex type horizontal separator with gravity filter for minimizing the dimension and mass of the separator. There are also presented the experimental studies made on the basis of this equipment.